(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This study examines language acquisition, a complex process influenced by sociocultural variables, cognitive processes, and linguistic diversity, with an emphasis on Uzbek learners’ acquisition of English grammar. The analysis explores the complex dynamics shaped by verb morphology, pluralization patterns, and syntactic elements in Uzbek language structures. The study reveals subtle difficulties in learning English grammar and differences in syntactic patterns between Uzbek and English that require cognitive adjustment. Complex verb morphology in English creates obstacles for auxiliary usage and tense forms; pluralization patterns and phonological distinctions cause more difficulties. Uzbek learners’ English language growth depends on a variety of factors, including experiences with cultural immersion, linguistic support, and tailored instructional methodologies.